Annuloaortic Ectasia and Arteritis: Clinical Features, Treatments of Choice, and Causative Relations - Yuan,Shi-Min (2019)
Abstract The roles that aortitis plays in the development of annuloaortic ectasia (AAE) remain uncertain, while clinical features of AAE in arteritis are largely unknown. This study was designed to highlight the clinical features of AAE, the treatments of choice, and the causative relations between aortitis and AAE. The morphology of the aortic valve leaflets was normal in half of the patients, while the valves were thin and overstretched in the other half. Most patients had an aortic aneurysm. Half of the patients had severe aortic valve insufficiency, and one-quarter of them had dilation of the sinuses of Valsalva. Takayasu arteritis was prone to develop coronary artery lesions, whereas giant cell arteritis were not. Aortic branch lesions in Takayasu arteritis were stenotic or occlusive in 92.9% of the patients, while in giant cell arteritis, they were all dilated lesions. Most patients (94.7%) required surgical treatment with steroid therapy. However, long-term follow-up results showed a higher anastomotic dehiscence rate, particularly in patients with Takayasu arteritis. Further morphometric and pathological research on AAE in arteritis should be undertaken, and more feasible measures should be warranted for preventing postoperative anastomotic dehiscence.